Real process improvement using the CMMI - West, Michael (Software engineer) (Auerbach Publications, 2004)
"Real Process Improvement Using the CMMI®" provides real-world concepts and techniques for CMMI-based process improvement that are as effective as they are innovative. Professionals at all levels - from systems engineers to CEOs - will find a wealth of practical guidance and new ways to look at model-based process improvement, resulting in benefits for large and small organizations in many environments. Using plain language and enlightening illustrations, the author identifies the most critical concepts of the CMMI, and details how to turn these concepts into real process improvement